Radiofrequency ablation versus cryoablation for atrioventricular nodal re-entrant tachycardia in children: a value comparison. (18th April 2016) - Oster, Matthew E.; Yang, Zhou; Stewart-Huey, Kay; Glanville, Michelle; Porter, Arlene; Campbell, Robert; Webb, Brad; Strieper, Margaret
Abstract: Background: It is unclear whether cryoablation or radiofrequency ablation offers better value for treating atrioventricular nodal re-entrant tachycardia in children. We aimed to compare the value of these procedures for treating atrioventricular nodal re-entrant tachycardia in children, with value being outcomes relative to costs. Methods: We performed a retrospective cohort study of all atrioventricular nodal re-entrant tachycardia ablations for children (age⩽18 years) from July, 2009 to June, 2011 at our institution. Costs included fixed costs, miscellaneous hospital costs, and labour costs, and key outcomes were acute and long-term success (6 months) of the ablations. We conducted T-tests and regression analyses to investigate the associations between the ablation procedure type and the cost and success of the ablations. Results: Of 96 unique cases performed by three paediatric electrophysiologists, 48 were cryoablation only, 42 radiofrequency ablation only, and six were a combination. Acute success was 100% for the cryoablation only and radiofrequency ablation only cases and 83% for the combination cases. There were no notable adverse events. The average total cost was $9636 for cryoablation cases, $9708 for radiofrequency ablation cases, and $10, 967 for combination cases (p=0.51 for cryoablation only versus radiofrequency ablation only). The long-term success rate was 79.1% for cryoablation only, 92.8% for radiofrequency ablation only, and 66.7% for the combination (p=0.01 for cryoablation only versus radiofrequency ablation only), but long-term success varied notably by provider. Conclusions: Cryoablation and radiofrequency ablation offer similar value in the short term for the treatment of atrioventricular nodal re-entrant tachycardia in children. Differences in long-term success may vary substantially by physician, and thus may lead to differences in long-term value.